Antipsychotic Treatment of Behavioral and Psychological Symptoms of Dementia (BPSD): Management of Extrapyramidal Side Effects - Ohno, Yukihiro; Kunisawa, Naofumi; Shimizu, Saki (Frontiers in Pharmacology, 2019)
Antipsychotic drugs are often used for the treatment of behavioral and psychological symptoms of dementia (BPSD), especially psychosis and behavioral disturbances (e.g., aggression and agitation). They are prescribed alone or in conjunction with anti-dementia (e.g., anti-Alzheimer’s disease drugs) and other psychotropic drugs (e.g., antidepressants). However, antipsychotic drugs frequently produce serious extrapyramidal side effects (EPS) including parkinsonian symptoms (e.g., bradykinesia, akinesia, tremor and muscle rigidity). Therefore, appropriate drug choice and combination strategy are important in the treatment of BPSD. Among anti-Alzheimer’s disease drugs, cholinesterase inhibitors (ChEIs, e.g., donepezil and galantamine) have a propensity to potentiate EPS associated with antipsychotic treatment in a synergistic manner. In contrast, the NMDA receptor antagonist memantine reduces antipsychotic-induced EPS. Antidepressant drugs, which inhibit 5-HT reuptake into the nerve terminals, also synergistically augment antipsychotic-induced EPS, while mirtazapine (2, 5-HT2 and 5-HT3 antagonist) reduces the EPS induction. Importantly, previous studies showed that multiple 5-HT receptors play crucial roles in modulating EPS associated with antipsychotic treatment. Specifically, activation of 5-HT1A receptors or blockade of 5-HT2, 5-HT3 and 5-HT6 receptors can alleviate EPS induction both by antipsychotics alone and by combining antipsychotic treatments with ChEIs or 5-HT reuptake inhibitors. In this article, we review antipsychotic use in treating BPSD and discuss the favorable drug selection in terms of the management of antipsychotic-induced EPS.